1999
DOI: 10.1255/jnirs.251
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Grain Weevils inside Single Wheat Kernels by a Very near Infrared Two-Wavelength Model

Abstract: Near infrared reflectance spectroscopy in the very near infrared region (700 nm to 1100 nm) has been investigated for the detection of grain weevil larvae and pupae inside single wheat kernels. Using a total of 80 samples, simple, two-wavelength classification models have been identified, based on either log 1/R (982 nm)-log 1/R (1014 nm) or log 1/R (972 nm)-log 1/R (1032 nm). Both models correctly classified over 96% of samples as uninfested or infested. Detection performance equalled that obtained using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 7 publications
4
21
0
Order By: Relevance
“…NIR spectroscopy is based on the molecular overtone and combination vibrations in organic compounds. In a previous study, by Ridgway et al, 28 wavelengths of 982 and 1014 nm were selected to develop a two-wavelength classification model for insect-damaged wheat kernels with NIR reflectance spectroscopy. Furthermore, Perez-Mendoza et al 29 found 890 nm to be one of the significant wavelengths for detecting insect fragments in wheat flour.…”
Section: Feature Extractionmentioning
confidence: 99%
“…NIR spectroscopy is based on the molecular overtone and combination vibrations in organic compounds. In a previous study, by Ridgway et al, 28 wavelengths of 982 and 1014 nm were selected to develop a two-wavelength classification model for insect-damaged wheat kernels with NIR reflectance spectroscopy. Furthermore, Perez-Mendoza et al 29 found 890 nm to be one of the significant wavelengths for detecting insect fragments in wheat flour.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Recent research on single wheat kernel quality measurement using NIR spectroscopy has successfully measured protein content (Delwiche 1995(Delwiche , 1998; wheat class (Song et al 1995;Delwiche and Massie 1996); color class (Dowell 1997(Dowell , 1998Wang et al 1999a-c); and insect damage Baker et al 1999;Ridgway et al 1999). However, the use of NIR spectroscopy to measure kernel heat damage, especially in combination with other quality measurements, has not been studied.…”
mentioning
confidence: 99%
“…The region between 2200 and 2300 nm is related with C-H and CONH 2 associated with several compounds including protein, starch and cell wall constituents (e.g. lignin) (Gergely and Salgo, 2005;Jacobsen et al, 2005;Ridgway et al, 1999;Workman and Weyer, 2008). Table 3 shows the calibration statistics for the PLS models developed for water uptake and steeping time using whole barley samples and NIR spectra after second derivative as pre-processing.…”
Section: Discussionmentioning
confidence: 99%